Challenging Lecturer Assumptions About Preservice Teacher Learning in Mandatory Indigenous Studies - Katrina Thorpe; Cathie Burgess (The Australian Journal of Indigenous Education, 2016)
This paper explores and challenges our assumptions as lecturers about preservice teachers’ knowledge and beliefs entering a mandatory Indigenous Studies subject. A total of 38 focus groups were conducted over two years (2011–2012) with preservice teachers enrolled in teaching degrees at the University of Sydney. Findings were analysed to identify and critically reflect on our assumptions about preservice teachers' prior understanding of the content and approaches to learning. To challenge our assumptions, this paper applies Brookfield's (1995) student and autobiographical lenses to engage in critical reflection and Nakata's (2002, 2007) ‘cultural interface’ to better understand the complexities, tensions and transformations that occur for learners in the Indigenous Studies classroom. Findings illuminated that assumptions about the level of resistance and indifference to course content were often overstated and rather, many preservice teachers were more likely to be insecure and reticent to express their ideas in this complex and potentially uncomfortable learning environment. Implications from the study highlight the need for ongoing critical reflection of lecturer assumptions about preservice teachers’ dispositions and how they engage with the subject to better understand the diversity of their knowledge and experiences and what this means for teaching and learning in this context.